PENGARUH STRATEGI PEMASARAN, FASILITAS OUTLET DAN HARGA TERHADAP KEPUASAN PELANGGAN STUDI KASUS PADA OUTLET DEAR SISTERS SIDOARJO - Dandi Prasetyo Atmojo; Pompong Budi Setiadi; Sri Rahayu (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of marketing strategy, outlet facilities and prices on customer satisfaction. This research was conducted at the Dear Sisters outlet in Sidoarjo, East Java. The research method used in this research is descriptive by using quantitative methods. This study uses primary data, namely the distribution of questionnaires by taking respondents from the Dear Sisters outlet customers in the Sidoarjo branch, East Java. This study uses random sampling with a total of 50 respondents from Dear Sisters outlet customers. The analytical method used is multiple regression analysis which is processed using the SPSS application. The results of this study indicate that the marketing strategy variable has no effect on customer satisfaction, the outlet facility variable has a positive effect on customer satisfaction and the price variable has no effect on customer satisfaction. And the variables of marketing strategy, outlet facilities, and prices simultaneously affect customer satisfaction.